Dynamic Marketing Capability: Science Mapping Based on Bibliometric Analysis - Asmawati; Mursalim Nohong (IECON: International Economics and Business Conference, 2023)
Dynamic marketing capabilities (DMC) are critical for small and medium enterprises (SMEs) on their way to enter international markets. This study provides an in-depth explanation of bibliometric analysis, which contributes to various literatures by examiningthe research features of dynamic marketing capabilities. Aims to analyze scientific mapping related to keywords. by utilizing the puplish or perish (PoP) software the google shoolar database is then visualized on the VOSviewer device. Searches were performedwith the keywords “dynamic marketing capabilities” OR “DMC' without specifying a year. The result is that there are 15 articles starting in 2011 – 2022, in the last five years there has been very little research on dynamic marketing capabilities, namely 8 articles, This is obtained from the results of the analysis in table 3. Based on data collected from the Google Scholar database, over the past10 years there has not been found any research that examines Bibliometric analysis on the topic of dynamic marketing capabilitiesin Indonesia. Furthermore, bibliometric analysis of citations shows the contribution of article publishers in the past year. Of the 8 articles in table 3, only the top three articles have the highest number of citations which are the biggest contributors to research onthe topic of dynamic marketing capabilities.